Down-the-line from the Persian Gulf to the Armenian Highlands: Archaeomalacology as a tool for the recognition of long-distance connections during the Middle Bronze Age - Cesaretti, Andrea; Flavia Gravina, Maria; Dan, Roberto (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
This article analyses a series of shells found over the years in a number of burials in the Armenian Highlands. These are tombs within some of the most important Middle Bronze Age funerary contexts, such as Lori berd, Lchashen, Verin Naver and Karashamb. The discovery of shells, although apparently of minor importance compared to other well-known and studied objects present among the grave goods of these burials allows important information to be reconstructed. In particular, these molluscs, which come from places very far from the mountains of the Armenian Highlands, demonstrate that the Middle Bronze Age communities had direct or indirect relationships with very distant territories, such as the Mediterranean Sea and the Persian Gulf.